Effect of Vitamin D Deficiency on Gestational Diabetes Mellitus: A Meta-Analysis - Dian Handayani; Eti Poncorini Pamungkasari; Bhisma Murti (Masters Program in Public Health, 2023)
Background: Gestational diabetes mellitus increases the risk of a number of short-term and long-term health problems in both mother and baby. Some evidence states that one of the causes of gestational diabetes mellitus is vitamin D deficiency. This study aimed to estimate the magnitude of the influence of vitamin D deficiency on the incidence of gestational diabetes mellitus, through a meta-analysis of previous primary studies. Subjects and Method: This was a systematic review and meta-analysis with the following PICO, population: pregnant women, intervention: vitamin D deficiency, comparison: no vitamin D deficiency, outcome: gestational diabetes mellitus. The articles used in this study were obtained from four databases, namely PubMed, Google Scholar, Science Direct, and Springer Link, using the search keys